Update of the Venus density and temperature profiles at high altitude measured by SOIR on board Venus Express. (August 2015) - Mahieux, A.; Vandaele, A.C.; Bougher, S.W.; Drummond, R.; Robert, S.; Wilquet, V.; Chamberlain, S; Piccialli, A.; Montmessin, F.; Tellmann, S.; Pätzold, M.; Häusler, B.; et al.
Abstract: The SOIR instrument on board Venus Express regularly sounds the Venus atmosphere using the solar occultation technique. The density and temperature profiles are inferred from SOIR spectra recorded in the infrared. The method has been described in a previous publication (Mahieux et al., 2012. J. Geophys. Res. 117. doi:10.1029/2012JE004058.). This paper is devoted to the update of the VAST (Venus Atmosphere from SOIR measurements at the Terminator) compilation that was initiated in the above cited work, which gives the mean CO2 number density and temperature profiles for different latitude bins. The method has been improved and has been applied to more data. The new compilation which is given on the same latitudinal grid now distinguishes between the two sides of the terminator. The compilation also confirms the main thermal layering characteristics that were identified in the earlier version: the succession of a warm layer (230±30 K, 1− σ standard deviation) at a pressure level of 3.2×10 −7  mbar (~140 km), a very cold layer (125±32 K) at 2.5×10 −5  mbar (~123 km), a warm layer (204±17 K) at 0.01 mbar (~102 km) and finally a colder layer at 0.4 mbar (171±34 K, ~87 km). The layering of all the temperature profiles is explained by radiative rather than dynamical processes. The temporal temperature variation is larger than the mean latitudinal temperature variation. VAST is compared with temperature profiles obtained from other Venus Express instruments, VeRa and SPICAV–UV, and ground based measurements. Highlights: Mesosphere and lower thermosphere Venus terminator temperature profiles. Latitude variations studied. Permanent very cold layer at 125 km.